Pain and body position on the bicycle in competitive and recreational road cyclists: A retrospective study - Bini, R. R.; Hunter, J. R. (Sports Biomechanics, 2023)
This study compared the presence of pain in recreational and competitive road cyclists and body position on the bicycle between cyclists with and without pain. Seventy-one cyclists completed a survey reporting existing cycling-related sites of pain and comfort. Static sagittal and frontal plane images were taken to analyse body position on the bicycle. Participants were separated into recreational and competitive road cycling groups, and further into cyclists reporting pain in the upper body, low back, buttocks/hips and knees for comparison with cyclists without pain. A logistic regression model investigated possible predictors of pain whilst cycling. Pain was present in 67% of recreational and 70% of competitive cyclists whilst comfort was reported by 81% of recreational and 75% of competitive cyclists. Trivial to moderate non-significant differences were observed for body position on the bicycle between cyclists with and without pain, and between cyclists with and without pain in the upper body, low back, buttocks/hips and knees. The predictive logistic model was not significant (p = 0.07) with a model fit predicted by McFadden R³ of 0.07. Given most cyclists reported both pain and comfort, comfort is probably not a good predictor of overuse injury risk.